In Silico and In Vitro Investigation of Cytotoxicity and Apoptosis of Acridine/Sulfonamide Hybrids Targeting Topoisomerases I and II - Mohamed Badr; Elshaymaa I. Elmongy; Doaa Elkhateeb; Yasmine S. Moemen; Ashraf Khalil; Hadeer Ali; Reem Binsuwaidan; Feby Awadallah; Ibrahim El Tantawy El Sayed (MDPI AG, 2024)
Background: Sulfonamide acridine derivatives have garnered significant attention from medicinal chemists due to their diverse range of biological activities. Methods: In this study, eleven compounds were synthesized according to the literature, and their impact on cell growth inhibition, induction of apoptosis, and cell cycle distribution were assessed in three different cell lines. Their inhibitory effects on the topoisomerase (Topo) I and II were investigated in vitro. Molecular docking studies were conducted to predict the binding affinities of these compounds for crystallized downloaded topoisomerases. Results: The compounds were examined in vitro for their anticancer activity against human hepatic (HepG2) colon (HCT-8) and breast (MCF-7) carcinoma cell lines. Compound 8b was the most active against HepG2, HCT-116, and MCF-7 with IC50 14.51, 9.39, and 8.83 µM, respectively, compared to Doxorubicin as reference. In addition, it demonstrated the highest potency among the tested compounds against Topo-I, with an IC50 value of 3.41 µg/mL compared to the control camptothecin (IC50 of 1.46 μM). Compound 7c displayed a significant inhibitory effect on Topo-II, with an IC50 of 7.33 μM, compared to an IC50 value of 6.49 μM via Doxorubicin, the control. Compounds 7c and 8b were assessed against topoisomerases showing induction of apoptosis and a reduction in the S phase of the cell cycle. Molecular docking demonstrated interaction with the active site as with those exhibited by the co-crystallized ligands of the crystallized proteins in both topoisomerases. Conclusion: Compounds 7c and 8b hold promise as potential anticancer drugs due to their anti-proliferative and proapoptotic effects, which are mediated by their action on the topoisomerase enzyme, particularly Topo II.